Short term gold-mine tailings exposure induced growth and photosynthesis of Philippine Tung (Reutealis trisperma [Blanco]) - Hamim, Hamim; Pranowo, Dibyo; Setyaningsih, Luluk; Muhammad Hilmi; Saprudin, Deden (Penerbit Universiti Kebangsaan Malaysia, 2020)
Philippine Tung (Reutealis trisperma [Blanco] Airy Shaw) is one of non-edible oil producing plant resistant to unfavorable conditions and therefore this plant has prospective role to be used in phytoremediation program on gold post-mined area. The experiment aimed to analyze photosynthesis and growth of R. trisperma plants in response to short term gold-mine tailing treatment in polybag experiment. The experiment was carried out using completely randomized design with two factors and 5 replications. The first factor was five varieties of R. trisperma (M1, M2, D1, D2 and HR) and the second factor was gold-mine tailings treatment comprised 0, 25, 50, and 100% of tailings which was applied in combination with mixed compost and soil 1:3 (v/v) as a basic media. Plant growth and physiological characters were observed after 6 weeks of the treatment. The result showed that even though malondialdehyde (MDA) of R. trisperma leaves increased slightly, but the plants treated with gold-mine tailing had higher photosynthetic rate than that of the control (untreated) plants, which resulted in the improvement of root and shoot growth up to 70 and 90%, respectively. Higher content of Ca, Mg, Fe, Zn, and Mn in gold-mine tailing may have positive effect to R. trisperma indicated by photosynthesis and growth enhancement which suggests the plant tolerance to gold-mine tailings.